Pengaruh Kualitas Produk, Usability dan Responsiveness Chatbot terhadap Kepuasan Konsumen Roughneck 1991 di Shopee - Sumampouw, Jhovan Davidson Frebert; Meliana, Vina (KALBISOCIO Jurnal Bisnis dan Komunikasi, 2026)
This study aims to analyze the influence of product quality, chatbot usage, and chatbot responsiveness on customer satisfaction with Roughneck 1991 on the Shopee marketplace. A quantitative research method was employed by distributing questionnaires to 160 individuals who had previously purchased Roughneck 1991 products and used its chatbot feature on Shopee. The data were collected using purposive sampling and analyzed through multiple linear regression to determine the extent to which the three variables contribute to customer satisfaction. The results show that product quality has a significant effect on customer satisfaction, chatbot usage significantly affects customer satisfaction, and chatbot responsiveness also has a significant influence on customer satisfaction. The study concludes that product quality is the most dominant factor influencing customer satisfaction, followed by chatbot usage and chatbot responsiveness. These findings provide practical implications for the Roughneck 1991 brand in optimizing its marketplace sales strategy by enhancing product quality and further developing its chatbot features.